Mucinous biliary obstruction associated with a cholangiocarcinoma - Necmettin KARAEREN; Can UYGURER; Ergün SARAÇOĞLU; Celalettin ÇETİN and Sait BAĞCI and Mustafa GÜLŞEN and Ahmet UYGUN and Kemal DAĞALP and Burhan ŞAHİN and Ahmet ALPER (Turkish Journal of Gastroenterology, 2019)
-